ANALISIS PENGARUH KENDARAAN OVER DIMENSI DAN OVER LOADING - Thadeus Raphael Gunawan; Amalia Kurniawan; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2023)
Over Dimension Over Load (ODOL) is an excess load on the vehicle. By definition, overload is a condition in which a vehicle carries a load that exceeds the specified load limit. While Overdimension is a condition where the dimensions of the vehicle carrier are not in accordance with production standards and regulatory provisions. The many negative impacts caused by ODOL; policy intervention is needed so that the target of zero ODOL can be realized immediately. This research is qualitative research that is a literature study (library research) that uses books and other literature as the main research object. The results of this study conclude that the zero ODOL policy must be realized immediately because many roads are damaged which causes many accidents, but requires joint awareness of the importance of implementing this policy